Improving Credit Information, Bank Regulation, and Supervision: On the Role and Design of Public Credit Registries - Powell, Andrew; Mylenko, Nataliya; Miller, Margaret; Majnoni, Giovanni (World Bank, Washington, D.C., 2013)
The authors analyze how data in public credit registries can be used both to strengthen bank supervision and to improve the quality of credit analysis by financial institutions. Empirical tests using public credit registry (PCR) data were performed in collaboration with the central banks in Argentina, Brazil, and Mexico. The results of the empirical tests confirm the value of the data for credit risk evaluation and provide insights regarding its use in supervision, including in calculations of credit risk for capital and provisioning requirements, or as a check on a bank's internal ratings for the Basel II's internal rating-based approach. The authors also define a set of critical design parameters and use the results to comment on appropriate public registry design. Finally, they discuss the relationship between the different objectives of a PCR and how they influence the registry's design.